2018
DOI: 10.15578/jra.13.1.2018.85-92
|View full text |Cite
|
Sign up to set email alerts
|

STUDI KASUS INFEKSI TILAPIA LAKE VIRUS (TiLV) PADA IKAN NILA (Oreochromis niloticus)

Abstract: ABSTRAKIkan nila atau Oreochromis niloticus merupakan ikan konsumsi masyarakat di Indonesia. Kasus kematian massal ikan nila terjadi di beberapa lokasi budaya di Jawa, Lombok, dan Sumatera yang disebabkan oleh infeksi Orthomyxovirus, dan disebut sebagai Tilapia Lake Virus (TiLV). Tujuan penelitian ini adalah untuk mendeteksi adanya infeksi TiLV dengan metode semi-nested Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) pada kasus kematian massal ikan nila. Lokasi pengambilan sampel di Desa Sigerongan Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 10 publications
0
30
0
6
Order By: Relevance
“…There are various aspects to these methods that warrant specific discussion. TiLV has been identified in fish spanning a variety sizes 9,12,14,15,49 and species of tilapia so far, including farmed hybrid tilapia (O. niloticus x O. aureus) 11,14 , Nile tilapia (O. niloticus) 9,10,14,15,16,33,35,36,49,50 and red tilapia (Oreochromis sp.) 16,33,48,51 , as well as in wild Nile tilapia 9,12 , black tilapia 51 , T. zilli 14,15 , S. galilaeus, O. aureus and T. simonis intermedia 14 and very recently TiLV was identified in wild carp (Barbonymus schwanenfeldii) 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various aspects to these methods that warrant specific discussion. TiLV has been identified in fish spanning a variety sizes 9,12,14,15,49 and species of tilapia so far, including farmed hybrid tilapia (O. niloticus x O. aureus) 11,14 , Nile tilapia (O. niloticus) 9,10,14,15,16,33,35,36,49,50 and red tilapia (Oreochromis sp.) 16,33,48,51 , as well as in wild Nile tilapia 9,12 , black tilapia 51 , T. zilli 14,15 , S. galilaeus, O. aureus and T. simonis intermedia 14 and very recently TiLV was identified in wild carp (Barbonymus schwanenfeldii) 52 .…”
Section: Discussionmentioning
confidence: 99%
“…This disease has serious socio-economic consequences and is a direct threat on food security for millions of people in Africa 7 , Asia and South America. At the start of 2018, the World Organization for Animal Health (OIE) reported that the etiological agent of this disease, TiLV, had been officially detected on three continents covering eight countries 8 and since this pathogen information card was updated there have been more reports of TiLV in Tanzania, Uganda 9 , Indonesia 10 , Taiwan 11 and Peru 12 . TiLV is a novel single-stranded RNA virus described to be an orthomyxo-like virus because it contains a variety of characteristics reminiscent of other orthomyoxoviruses such as Influenza or Infectious salmon anaemia virus (ISAV) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Since 2014, strains of tilapia lake virus (TiLV) have spread globally, causing 10 to 90% mortality in cultured tilapia ( Oreochromis spp. and hybrids) fry, juveniles, and adults in Colombia ( 1 ), Ecuador ( 2 ), Egypt ( 3 ), India ( 4 ), Indonesia ( 5 ), Israel ( 6 ), Malaysia ( 7 ), the Philippines ( 8 ), Peru ( 9 ), Tanzania ( 10 ), Thailand ( 11 ), Taiwan Province of China ( 12 ), and Uganda ( 13 ). Clinical signs associated with TiLV infections include lethargy, anorexia, and swimming at the surface away from schooling tankmates.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Since 2014, there have been global reports of TiLV disease resulting in 10-90% mortality in tilapia fry, juveniles, and adults causing significant economic losses (Fathi et al 2017 andJensen et al 2018). Currently, the disease has been confirmed in Colombia (Kembou Tsofack et al 2017), Ecuador (Ferguson et al 2014, Subramaniam et al 2019, Egypt (Nicholson et al 2017), India (Behera et al 2018), Indonesia (Koesharyani et al 2018), Israel (Eyngor et al 2014, Malaysia (OIE, 2017a), Mexico (OIE 2018a), Philippines (OIE, 2017b), Peru (OIE, 2018b), Tanzania (Mugimba et al 2018), and Thailand (Surachetpong et al 2017). Despite the global detection of TiLV, it has not yet been found in the United States or Canada.…”
Section: Introductionmentioning
confidence: 99%